2003
DOI: 10.1007/s00221-003-1453-1
|View full text |Cite
|
Sign up to set email alerts
|

Motor planning: effect of directional uncertainty with discrete spatial cues

Abstract: We investigated the effect of spatial uncertainty on motor planning by using the cueing method in a reaching task (experiment 1). Discrete spatial cues indicated the different locations in which the target could be presented. The number of cues as well as their direction changed from trial to trial. We tested the adequacy of two models of motor planning to account for the data. The switching model assumes that only one motor response can be planned at a time, whereas the capacity-sharing model assumes that mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 47 publications
6
23
0
Order By: Relevance
“…The analyses indicated that RT was significantly affected by number of cues (F (2,4) ϭ 24.730; p ϭ 0.006), whereas MT was not (F (2,4) ϭ 0.186; p ϭ 0.837). As expected, these results show that increasing the number of possible target locations increased RT, which is consistent with the results obtained previously with a similar experimental paradigm (Pellizzer and Hedges, 2003;Pellizzer et al, 2006).…”
Section: Behavioral Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The analyses indicated that RT was significantly affected by number of cues (F (2,4) ϭ 24.730; p ϭ 0.006), whereas MT was not (F (2,4) ϭ 0.186; p ϭ 0.837). As expected, these results show that increasing the number of possible target locations increased RT, which is consistent with the results obtained previously with a similar experimental paradigm (Pellizzer and Hedges, 2003;Pellizzer et al, 2006).…”
Section: Behavioral Resultssupporting
confidence: 93%
“…For example, it is known that the latency of motor responses increases progressively with the number of possible movement directions, which indicates that the level of motor preparation covaries with the degree of directional uncertainty (Bock and Arnold, 1992;Basso and Wurtz, 1998;Dorris and Munoz, 1998;Pellizzer and Hedges, 2003;Kveraga et al, 2006;Pellizzer et al, 2006;Churchland et al, 2008). Consequently, if both response latency and beta-band ERD reflect the complexity of motor preparation, we expect beta-band ERD to be modulated by directional uncertainty as well.…”
Section: Introductionmentioning
confidence: 99%
“…The Area, Decision Changes, Number of Submovements and Maximum Velocity (Fig. 4B) evidently varied in accordance with MT’s changes, as has been reported in other studies [25], [26]. This pattern can be due to subjects beginning their movement before they reach a decision (shorter RT) and deciding while they move (longer MT) as long as targets are close to each other, since in this case a slight trajectory modification would be enough to reach the desired target.…”
Section: Resultssupporting
confidence: 88%
“…A few previous studies have also used a delay between target exposition and response signal. Similar to the present study, Pellizzer and Hedges (2003) found, for their two-target condition, no effect of target separation. Praamstra et al (2009) reported extremely small (Ͻ10 ms) effects.…”
Section: Discussionsupporting
confidence: 90%